Rate-induced tipping in natural and human systems - P. D. L. Ritchie; P. D. L. Ritchie; H. Alkhayuon; P. M. Cox; P. M. Cox; S. Wieczorek (Earth System Dynamics, 2023)
Over the last 2 decades, tipping points in open systems subject to changing external conditions have become a topic of a heated scientific debate due to the devastating consequences that they may have on natural and human systems. Tipping points are generally believed to be associated with a system bifurcation at some critical level of external conditions. When changing external conditions across a critical level, the system undergoes an abrupt transition to an alternative, and often less desirable, state. The main message of this paper is that the rate of change in external conditions is arguably of even greater relevance in the human-dominated Anthropocene but is rarely examined as a potential sole mechanism for tipping points. Thus, we address the related phenomenon of rate-induced tipping: an instability that occurs when external conditions vary faster, or sometimes slower, than some critical rate, usually without crossing any critical levels (bifurcations). First, we explain when to expect rate-induced tipping. Then, we use three illustrative and distinctive examples of differing complexity to highlight the universal and generic properties of rate-induced tipping in a range of natural and human systems.